GST hike from 3% to 4% : a study of household perceptions and its impact on household expenditure - Ku, Zhi You (2008)
The report’s objective was to determine the impact of the 3%-4% GST hike on household expenditure/consumption patterns of Singaporeans/Permanent-Residents. 3 groups were examined, namely the low, middle and high-income. Their perceived impact of the GST hike on general price level, purchasing power and adequacy of the offsets were also sought.